Effect of compounds isolated from natural products on IFN-γ/LPS- induced nitric oxide production in RAW 264.7 macrophages - Ahmad, Syahida; Ahmad Israf, Daud; Lajis, Nordin; Shaari, Khozirah; Mohamad, Habsah; Karim, Jasril; Permana, Dharma; I., Norhadiani (Taylor & Francis, 2006)
The current study was designed to evaluate whether compounds isolated from local medicinal plants in Malaysia suppressed nitric oxide (NO) production in inflammation. The murine monocytic macrophage (RAW 264.7) cell line was used as a target cell and activated by interferon-γ. (IFN-γ.) and lipopolysaccharide (LPS). Our current study has identified four phytochemicals, namely atrovirinone, cardamonin, flavokawin B, and zerumbone, that inhibit pathological NO generation. These compounds are candidates for further bioassay studies to determine their suitability as drug leads.